2022
DOI: 10.3390/ijms232314779
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Insights into Gastrointestinal Dysfunction in Myotonic Dystrophy Types 1 & 2

Abstract: Myotonic dystrophy (DM) is a highly variable, multisystemic disorder that clinically affects one in 8000 individuals. While research has predominantly focused on the symptoms and pathological mechanisms affecting striated muscle and brain, DM patient surveys have identified a high prevalence for gastrointestinal (GI) symptoms amongst affected individuals. Clinical studies have identified chronic and progressive dysfunction of the esophagus, stomach, liver and gallbladder, small and large intestine, and rectum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 158 publications
0
8
0
Order By: Relevance
“…Furthermore, the SMC transcription factor MYOCD was recently found to indirectly drive a set of SMC AS changes via changes in the expression levels of RBPMS, RBFOX2 and MBNL1 (Liu et al, 2022), and both Rbpms and Mbnl1 were found by scRNA-Seq to be part of a contractile VSMC gene signature (Dobnikar et al, 2018). Indeed, it has been suggested that gastrointestinal dysfunction in myotonic dystrophy is associated with dysregulation of an MBNL1 regulated splicing program in visceral smooth muscle cells (Peterson & Cooper, 2022). Our data suggest that this dysregulated program is likely driven by MBNL1-RBPMS coregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the SMC transcription factor MYOCD was recently found to indirectly drive a set of SMC AS changes via changes in the expression levels of RBPMS, RBFOX2 and MBNL1 (Liu et al, 2022), and both Rbpms and Mbnl1 were found by scRNA-Seq to be part of a contractile VSMC gene signature (Dobnikar et al, 2018). Indeed, it has been suggested that gastrointestinal dysfunction in myotonic dystrophy is associated with dysregulation of an MBNL1 regulated splicing program in visceral smooth muscle cells (Peterson & Cooper, 2022). Our data suggest that this dysregulated program is likely driven by MBNL1-RBPMS coregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal gallbladder releases were found in individuals with DM1 administered with cholecystokinin to stimulate release and rates of cholelithiasis are increased in DM1 cohorts 2,16 . In the liver, abnormal levels of alkaline phosphatase, alanine aminotransferase, gamma-glutamyl transferase, and 5' nucleotidase were present 2,16 . Although relatively nonprogressive as a condition, such enzymes can lead to cholestasis and hepatocellular damage 2,16 .…”
Section: Gastrointestinal Systemmentioning
confidence: 99%
“…Between 48-55% of individuals experience swallowing difficulties; between 33-46% experience constipation; between 38-39% of individuals experience acid reflux, making these the most common GI-related symptoms experienced 16 . Barium swallows (where barium is tracked via x-ray after being swallowed to discover abnormalities in esophageal movements) reveal difficulty in the closing of nasal passages, along with a tendency for individuals to retain meals in the oropharyngeal recess, and upper, and lower esophagus as well 16 . In the stomach, DM1 presents a lowered rate of digestion through higher meal lag phases and slower gastric emptying 16 .…”
Section: Gastrointestinal Systemmentioning
confidence: 99%
See 2 more Smart Citations